Lateinische Gedichte im Urtext mit den schönsten Übertragungen deutscher Dichter - Rüdiger, Horst; Rüdiger, Horst (Sammlung Tusculum, 2014)
Frontmatter -- Vorwort -- QUINTUS HORATIUS FLACCUS / Schlegel, August Wilhelm v. -- COLLECTIO DISTICHORUM VULGARIS / Opitz, Martin -- TITUS LUCRETIUS CARUS / Rode, August v. / Wieland, Christoph Martin / Knebel, Karl Ludwig v. / Humboldt, Wilhelm v. / Schlegel, August Wilhelm v. / Seydel, Max v. -- MARCUS VALERIUS MARTIALIS -- CAIUS VALERIUS CATULLUS / Götz, Johann Nikolaus / Immermann, Karl / Ramler, Karl Wilhelm / Mörike, Eduard / Herder, Johann Gottfried / Alxinger, Johann v. -- PUBLIUS VERGILIUS MARO -- PUBLIUS VERGILIUS MARO / Mörike, Eduard / Weckherlin, Georg Rudolf / Schröder, Rudolf Alexander / Beling, Oswald / Haecker, Theodor / Stolberg, Friedrich Leopold zu / Schiller, Friedrich v. / Voß, Johann Heinrich / Schlegel, August Wilhelm v. / Geibel, Emanuel -- QUINTUS HORATIUS FLACCUS -- QUINTUS HORATIUS FLACCUS / Opitz, Martin / Herder, Johann Gottfried / Platen, August v. / Gottsched, Louise Adelgunde Victorie / Geibel, Emanuel / Ramler, Karl Wilhelm / Lessing, Gotthold Ephraim / Hölderlin, Friedrich / Wobeser, Ernst Wratislaw Wilhelm v. / Schröder, Rudolf Alexander / Geibel, Emanuel / Klopstock, Friedrich Gottlieb / Hölderlin, Friedrich / Wieland, Christoph Martin -- DOMITIUS MARSUS -- ALBIUS TIBULLUS / Wieland, Christoph Martin / Voß, Johann Heinrich -- SULPICIA / Mörike, Eduard -- MARCUS VALERIUS MARTIALIS -- SEXTUS PROPERTIUS / Mörike, Eduard / Voß, Johann Heinrich / Ramler, Karl Wilhelm / Knebel, Karl Ludwig v. / Geibel, Emanuel / Opitz, Martin / Ense, Karl August Varnhagen v. -- PUBLIUS OVIDIUS NASO / Knebel, Karl Ludwig v. / Manso, Johann Caspar Friedrich / Bürger, Gottfried August / Herder, Johann Gottfried / Voß, Johann Heinrich / Schütz, Christian Gottfried / Mörike, Eduard / Schlegel, August Wilhelm v. / Geibel, Emanuel / Ηalberstadt, Albrecht ν. / Hölderlin, Friedrich / Alxinger, Johann von -- LUCIUS ANNAEUS SENECA / Opitz, Martin -- CAIUS PETRONIUS ARBITER / Rüdiger, Horst / Heinse, Wilhelm -- MARCUS VALERIUS MARTIALIS -- MARCUS VALERIUS MARTIALIS / Delius, Rudolf v. / Ramler, Karl Wilhelm / Opitz, Martin / Wechherlin, Georg Rudolf / Lessing, Gotthold Ephraim / Alxinger, Johann v. / Hölty, Ludwig Christoph Heinrich / Voß, Johann Heinrich / Hagedorn, Friedrich v. / Logau, Friedrich v. / Tscherning, Andreas / Weiße, Christian Felix -- MARCUS VALERIUS MARTIALIS -- AULUS PERSIUS FLACCUS / Morhof, Daniel Georg / Τscherning, Andreas / Opitz, Martin / Herder, Johann Gottfried -- DECIMUS IUNIUS IUVENALIS / Canitz, Rudolf Ludwig v. -- PUBLIUS AELIUS HADRIANUS IMPERATOR -- DECIMUS MAGNUS AUSONIUS / Bödmer, Johann Jakob / Herder, Johann Gottfried / Dahn, Felix / Gerlach, Wolfgang / Weckherlin, Georg Rudolf / Opitz, Martin / Czepko, Daniel v. / Leibniz, Gottfried Wilhelm v. / Wagner, D. / Gottsched, Johann Christoph / Voß, Johann Heinrich -- CLAUDIUS CLAUDIANUS / Messerschmid, Georg Friedrich -- NACHWORT -- ANMERKUNGEN -- INHALT